The European bison (Bison bonasus) as an indicatory species for the circulation of tick-borne encephalitis virus (TBEV) in natural foci in Poland - Krzysiak, Michał K; Anusz, Krzysztof; Konieczny, Andrzej; Rola, Jerzy; Salat, Jiri; Strakova, Petra; Olech, Wanda; Larska, Magdalena (Ticks and tick-borne diseases, 2021)
Tick-borne encephalitis (TBE) is one of the most common zoonotic diseases in Europe transmitted by Ixodidae vectors. While small mammals such as bank voles and ticks constitute the main reservoirs for virus transmission, large sylvatic species act as a food source for ticks. Cervids such as roe deer and red deer are considered sentinel species for TBE in natural foci. In addition, an increase of the population size and density of large wild mammals in an area corresponds to an increase in the tick burden and may potentially increase the prevalence of TBE virus (TBEV) in ticks and tick hosts and further exposure risk in humans. Humans are considered accidental hosts. The prevalence of TBE relies on interactions between host, vector and environment. The present study examines the exposure of the largest European herbivore, the European bison (Bison bonasus) to TBEV infection. Assessed using the IMMUNOZYM FSME ELISA (PROGEN), the overall TBEV seroprevalence was 62.7% in the 335 European bison that were studied. ELISA results were confirmed by the gold-standard virus neutralization test (VNT) with 98.7% sensitivity and thus giving a true prevalence of 63.5%. TBEV seroprevalence was significantly correlated to the origin, age group, sex, population type (free living/captive) and sanitary status (healthy/selectively eliminated/found dead/killed in accident) of the European bison in the univariable analysis. The highest seroprevalences were observed in the three largest north-eastern wild populations (Białowieska, Borecka and Knyszyńska forests), which corresponded with the highest incidence of human cases reported in the country. The risk of TBEV seropositivity increased with age and was higher in female and free-ranging European bison. Additionally, to the epidemiological investigation, the continuous detection of TBEV antibodies was studied by repetitive testing of animals over the course of 34 months. Two of six seropositive animals remained seropositive throughout the study. The presence of antibodies was followed throughout the study in seropositive European bison and for at least a year in animals that seroconverted during the observation period.
Keywords: Male; Seroepidemiologic Studies; séroepidemiologické studie; European bison; Wildlife; Poland; prevalence; Encephalitis Viruses, Tick-Borne; mužské pohlaví; incidence; TBEV; Encephalitis, Tick-Borne; Bison; Animals; ženské pohlaví; zvířata; klíšťová encefalitida; Tick-borne encephalitis virus; Prevalence; viry klíšťové encefalitidy; Seroprevalence; Female; Polsko; Incidence; bizon